Incidence and clinical profiles of COVID-19 pneumonia in pregnant women: A single-centre cohort study from Spain. (June 2020) - San-Juan, Rafael; Barbero, Patricia; Fernández-Ruiz, Mario; López-Medrano, Francisco; Lizasoáin, Manuel; Hernández-Jiménez, Pilar; Silva, José Tiago; Ruiz-Ruigómez, María; Corbella, Laura; Rodríguez-Goncer, Isabel; Folgueira, María Dolores; Lalueza, Antonio; et al.
Abstract: Background: Information regarding the incidence and characteristics of COVID-19 pneumonia amongst pregnant women is scarce. Methods: Single-centre experience with 32 pregnant women diagnosed with COVID-19 between March 5 to April 5, 2020 at Madrid, Spain. Findings: COVID-19 pneumonia was diagnosed in 61·5% (32/52) women. Only 18·7% (6/32) had some underlying condition (mostly asthma). Supplemental oxygen therapy was required in 18 patients (56·3%), with high-flow requirements in six (18·7%). Eight patients (25·0%) fulfilled the criteria for acute distress respiratory syndrome. Invasive mechanical ventilation was required in two patients (6·2%). Tocilizumab was administered in five patients (15·6%). Delivery was precipitated due to COVID-19 in three women (9·4%). All the newborns had a favourable outcome, with no cases of neonatal SARS-CoV-2 transmission. Severe cases of pneumonia requiring supplemental oxygen were more likely to exhibit bilateral alveolar or interstitial infiltrates on chest X-ray (55·6% vs. 0·0%; P -value = 0·003) and serum C-reactive protein (CRP) levels >10 mg/dL (33·0% vs. 0·0%; P -value = 0·05) at admission than those with no oxygen requirements. Interpretation: Pregnant women with COVID-19 have a high risk of developing pneumonia, with a severe course in more than half of cases. The presence of bilateral kung infiltrates and elevated serum CRP at admission may identify women at-risk of severe COVID-19 pneumonia. Funding: Instituto de Salud Carlos III (COV20/00, 181), Spanish Ministry of Science and Innovation.